Promoting Active Aging in Russia : Working Longer and More Productively - Levin, Victoria (World Bank, Washington, DC, 2015)
A shrinking working-age population will be the Russian Federations biggest demographic challenge in coming decades. With workers increasingly scarce, sustainable future economic development depends on Russias ability to bring into the labor force currently under-utilized groups, such as young mothers and older people, and to maximize the productivity of every worker. This study assesses the projected dynamics of the working-age population and how changes in labor force participation may affect the future workforce. It also assesses the potential contribution of individual factors to either facilitate or deter the participation of older Russians in the labor force. A review of disincentives for labor force participation in current social insurance programs and labor institutions is followed by policy proposals to help prolong the working lives of older adults.